The sovereignty paradox the norms and politics of international state building - Zaum, Dominik (Oxford Oxford University Press, 2007)
This book is a study of the normative framework underlying the international community's state building efforts. Through detailed case studies of policy making by the international administrations in Bosnia and Herzegovina, Kosovo, and East Timor, based on extensive interviews and work in the administrations, the book examines the nature of this normative framework, and highlights how norms shape the institutional choices of statebuilders, the relationship between international and local actors, and the exit strategies of international administrations. The book argues that a particular conception of sovereignty as responsibility has influenced the efforts of international administrations, and shows that their statebuilding activities are informed by the idea that post-conflict territories need to meet certain normative tests before they are considered legitimate internationally. The restructuring of political and administrative practices to help post-conflict territories to meet these tests creates a sovereignty paradox: international administrations compromise one element of sovereignty--the right to self-government--in order to implement domestic reforms to legitimize the authority of local political institutions, and thus strengthen their sovereignty.
Includes bibliographical references (p. 246-273) and index.
Keywords: Nation-building.